Application and Challenge of Multi-Source Spatial Data Fusion in Archaeology - Zhang, Xinyao (Transactions on Environment, Energy and Earth Sciences, 2024)
The paper explores the application of multi-source spatial data fusion in archaeology and analyzes its future challenges. It shows that multi-source spatial data fusion can help archaeologists discover, analyze and protect archaeological sites and their surroundings more accurately. However, the heterogeneity of data, the complexity of processing and analyzing, and the challenge of interdisciplinary cooperation are still notable issues. The aim of this paper is to investigate the application and role of multi-source spatial data fusion, to explore the challenges it faces, and to propose methods to address these challenges.